The Migraine-Ischemic Stroke Relation in Young Adults - Alessandro Pezzini; Elisabetta Del Zotto; Alessia Giossi; Irene Volonghi; Paolo Costa; Giorgio Dalla Volta; Alessandro Padovani (Stroke Research and Treatment)
In spite of the strong epidemiologic evidence linking migraine and ischemic stroke in young adults, the mechanisms explaining this association remain poorly understood. The observation that stroke occurs more frequently during the interictal phase of migraine prompts to speculation that an indirect relation between the two diseases might exist. In this regard, four major issues might be considered which may be summarized as follows: (1) the migraine-ischemic stroke relation is influenced by specific risk factors such as patent foramen ovale or endothelial dysfunction and more frequent in particular conditions like spontaneous cervical artery dissection; (2) migraine is associated with an increased prevalence of cardiovascular risk factors; (3) the link is caused by migraine-specific drugs; (4) migraine and ischemic vascular events are linked via a genetic component. In the present paper, we will review epidemiological studies, discuss potential mechanisms of migraine-induced stroke and comorbid ischemic stroke, and pose new research questions.